EVALUASI PENGGUNAAN AKTIVISME KPOP FANS DALAM MENDUKUNG PILIHAN POLITIK DI PILPRES 2024 - Islamiyah, Hanifah (Jurnal Keadilan Pemilu, 2024)
This article discusses the phenomenon of K-pop politicization on the X social media platform, with a focus on the Anies Bubble case during the 2024 Election in Indonesia. The research uses attribution theory to understand the motivations behind political activism in the K-pop fandom community. The research method used is a case study with qualitative descriptive analysis. Anies Bubble is an anonymous account on X that supports Anies Baswedan with a style and culture similar to K-pop fans. Although anonymous, this account played an important role in political campaigns and fundraising for the AMIN couple. The research highlights a pattern of anonymity in K-pop fandom culture, where fans want to separate their online identities from their real lives. K-pop fandom culture is also noted for its significant financial support of its idols, which often leads to mass consumerism and wastefulness. Fans not only idolize them emotionally, but also buy albums, merchandise, and collect photo cards as a form of financial support. The practice of exchanging "freebies" has also become popular among fans, showing their love and support for their idols. Additionally, the article discusses K-pop fans' concerns regarding political and social issues. They not only enjoy music, but are also active in seeking understanding about social and political issues. This phenomenon reflects new forces in social activism, especially among the younger generation who have wide access to social media and information technology. Thus, K-pop is not only an entertainment industry, but also a platform for fans to actively participate in emerging social debates and movements.